2020
DOI: 10.1093/ofid/ofaa511
|View full text |Cite
|
Sign up to set email alerts
|

Precipitous Fall in Common Respiratory Viral Infections During COVID-19

Abstract: In the midst of the COVID-19 pandemic, we were surprised to find that all other respiratory viral infections fell precipitously. The difference in respiratory viral infections during the 16-week period of our peak COVID-19 activity in 2020 (CDC weeks 14-29) was significantly lower than during the same period in the previous four years (a total of four infections versus an average of 138 infections, p<0.0001). We attribute this to widespread use of public health interventions including wearing face masks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Internationally, public health measures targeted at controlling transmission of SARS-CoV-2 have altered the epidemiology and seasonality of other respiratory viruses. [6][7][8][9] In WA, the initial SARS-CoV-2-associated public health measures were associated with a 98% reduction in RSV detections through winter 2020. 6 A subsequent interseasonal resurgence with unprecedented RSV detections was observed in WA during the southern hemisphere summer.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, public health measures targeted at controlling transmission of SARS-CoV-2 have altered the epidemiology and seasonality of other respiratory viruses. [6][7][8][9] In WA, the initial SARS-CoV-2-associated public health measures were associated with a 98% reduction in RSV detections through winter 2020. 6 A subsequent interseasonal resurgence with unprecedented RSV detections was observed in WA during the southern hemisphere summer.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Several studies during the pandemic have demonstrated a decline in medically attended acute respiratory illnesses (ARI) and decreased activity of seasonal respiratory viruses, including influenza. [6][7][8][9] Restrictions among available healthcare resources have also altered practice patterns (such as increased use of telemedicine) and clinical and research priorities to slow SARS-CoV-2 spread and alleviate stress on the healthcare system. 10,11 In addition, a decline in child vaccination coverage suggests that patients have been reluctant to procure healthcare during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies conducted soon after the onset of the pandemic and over shorter durations showed relatively quick declines in rates of viral infections or antimicrobial prescribing. [3][4][5][6] However, to our knowledge, this study is the first to combine respiratory virus activity and antibiotic prescriptions that were indexed to the number of encounters over a prolonged period that includes the typical respiratory virus season. The data suggest that COVID-19 transmission mitigation strategies may help curb respiratory viral diseases beyond SARS-CoV-2 and, indirectly, decrease antibiotic prescribing.…”
mentioning
confidence: 99%